Results of treatment of patients with fractures of low bones of their extremities in cases of multiple injuries by means of the method of blocking intramedullary osteosynthesis - Gerasimenko, Sergey; Baychuk, Bogdan; Arshulik, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
On the basis of experience of treatment of 52 patients with fractures of bones of the lower extremities with polytrauma by the method of interlocking intramedullary nailing (IIN), results of restoration of an extremity in the early and late postoperative periods were studied. Treatment of patients with polytrauma by IIN and osteosynthesis with superimposed plates was comparatively analysed. It was found out that stable-functional osteosynthesis of the femoral and tibial bones by means of mini-invasive technologies with use of interlocking intramedullary nails was the method of choice for treating this group of casualties.